In Vitro Antagonism between Phytopathogenic Fungi Sclerotium rolfsii and Trichoderma Strains - Parmar, H. J.; Hassan, Mohamed M.; Bodar, N. P.; Umrania, V. V.; Patel, S.V.; Lakhani, H.N. (International Journal of Applied Sciences and Biotechnology, 2015)
Six Trichoderma strains (collected from IARI, New Delhi and MTCC, Chandigarh) were tested for their ability to inhibit soil born pathogenof groundnut mainly Sclerotium rolfsii (causing stem rot on groundnut). Morphological observations of Trichoderma strains as well asphytopathogenic fungi S. rolfsii were made from culture grown at 28 0C for about one week on PDA media. The radial growth, fastest growthand coiling of test fungus of various Trichoderma strains on plant pathogenic fungi S. rolfsii were examined under LEICA phase contrastbinocular light microscope. In vitro percent growth inhibition of S.rolfsii by various Trichoderma strain was recorded at 5 days after inoculationat 28 oC in the 90 cm petriplates. Results obtained from the antagonism study indicated that Trichoderma viride (NBAII Tv 23) inhibited 61%growth of phytopathogenic fungi S. rolfsii followed by T. harzianum (NBAII Th1) (55% growth inhibition of pathogen). This suggested thatamong different Trichoderma strains, T. viride was the best bio-control agent to inhibit in vitro growth of phytopathogen S.rolfsii whichotherwise cause stem rot disease in groundnut.DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.11845  Int J Appl Sci Biotechnol, Vol. 3(1): 16-19